Exhaled nitric oxide is associated with postnatal adaptation to hypoxia in Tibetan and non‐Tibetan newborn infants. (5th February 2016) - Wu, Panpan; Shanminna,; Liang, Kun; Yue, Hongni; Qian, Liling; Sun, Bo
Abstract: Aim: This Chinese study assessed partial pressure of exhaled nitric oxide (PeNO) in healthy Tibetan and non‐Tibetan newborn infants born at a very high altitude. Methods: Full‐term Tibetan and non‐Tibetan neonates born in Lhasa, 3658 metres above sea level, were compared to non‐Tibetan neonates born in Kunming (1891 m) and Huai'an (16 m). The chemiluminiscence technique was used to measure the fraction of exhaled nitric oxide during spontaneous tidal breathing and this was then converted to partial pressure of exhaled nitric oxide (PeNO). Results: In their first week, Tibetan and non‐Tibetan neonates born in Lhasa had persistently higher PeNO levels than non‐Tibetan neonates born in Kunming and Huai'an, which was further verified by partial pressure of inspired oxygen adjustment. However, the non‐Tibetans born in Lhasa required short‐term oxygen therapy to improve their early postnatal oxygenation. The temporal changes of PeNO and cardio‐respiratory function measurements demonstrated that Tibetan and non‐Tibetan newborns in Lhasa initially needed to adapt to attain homoeostasis in oxygenation and gas exchange. Conclusion: Tibetan and non‐Tibetan newborn infants living at the same high altitude demonstrated comparable PeNO levels during postnatal adaptation to hypobaric hypoxia, which warrants further investigation of the mechanism of endogenous nitric oxide and hypoxic tolerance. Abstract :